Education, Democracy and Living With Disagreement - Gregory, Ian (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2019)
This paper will revisit issues to do with the roles of education and an ostensibly liberal democracy in a world rife with disagreement. It seems certain that the outcome of the revisiting will be an insistence that to be true to themselves, the provision of education at both the individual and societal level must cling hard to the key notions of truth, objectivity, and rational justification in a world that perhaps more than any other time is inclined to doubt whether in any final sense these notions have much going for them. Disagreement is the challenge and spur to the reaffirming of our belief in the importance of rational debate in both the private and public spheres.